Agroforestry Methods for Cultivation in Zagros Pasture Iran due to Conservation of Water Resource - Mollaei, Yousef Taghi (Indian Forester, 2018)
Most Of The Crop Plants Concerned Are Relatively Undemanding And Well Suited For Cultivation On Lighter Soils And Sites Tending Towards Dryness. They Can Be Well Integrated Into The Rotation Of Crops And Would Thus Increase The Agricultural Biodiversity Of These Sites Introduction. The Study Will Show The Change Crop Plants And Methods Of Cultivation In Khosroshirin Village Of Abadeh, Fars, Iran Due To Conservation Of Water Resource. As Alternative Methods Of Cultivation This Report Discusses Procedures Which Counteract The Ongoing Decoupling Of Crop Production From Natural Locational Factors And Thereby Tend To Make A Contribution To The Conservation Or The Recovery Of The Multifunctionality Of Agriculture. With Attitude To, Its Cold Weather Proposed, Â« Alley Cropping Â» Refers To A Method Of Cultivation, In Which The Combination Of Agricultural Crops With Perennial Plants Is Represented As An Agroforestry System.